(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the clinical and paraclinical characteristics of aseptic necrosis of the femoral head at Ha Tinh TTH General Hospital from 2022-2023. Method: Research using descriptive and analytical epidemiological methods. Results: 180 study patients had an average age of 54.7 years; male/female ratio is 8.47/1; 86.1% live in rural areas; 57.2% work in farming and 41.1% work in scuba diving. Clinical highlights include 89.4% of pain in the hip joint area; 96.1% had difficulty moving the hip joint; average time from injury to hospital admission was 19.70 ± 16.57 months; 100% muscle atrophy and limited movement; 56.6% had short limbs of 0.5 cm or more. Paraclinical results showed decreased bone density (42.2%) and osteoporosis (29.4%), average T-score value -1.74 ± 0.99; the highest proportion of lesions is grade III when taking MRI (57.2%) and when taking X-ray (46.6%). Conclusion: Aseptic necrosis of the femoral head mainly occurs in men, living in rural areas with symptoms of muscle atrophy, pain in the hip joint, limited mobility, decreased bone density or osteoporosis with T-score value -1.74 ± 0.99